12-month post-trial follow-up of participants in the Australian arm of the second low-dose colchicine trial. (14th October 2021) - Nidorf, S M; Budgeon, C; Eikelboom, J W; Murray, K; Nidorf, L; Thompson, P L; ,
Abstract: Background: In the Australian arm of the LoDoCo2 trial, colchicine 0.5mg daily compared with placebo markedly reduced the risk of cardiovascular (CV) events in patients with chronic coronary disease (2.0 vs 3.9 events per 100 person years, HR 0.51; 95% CI 0.39–0.67). The purpose of this analysis was to explore CV and non-CV outcomes in the Australian cohort out to one year after cessation of trial medication. Methods: Information was collected on all potential CV events and non-CV deaths as well as a range of other co-morbidities. All CV events were blindly adjudicated. The analysis examined the primary outcome (a composite of CV death, myocardial infarction, ischemic stroke, and unscheduled revascularization) and non-CV deaths by initial randomized treatment from the beginning of the trial up until one year after cessation of trial medication. A landmark analysis was then used to examine these outcomes from the date of last contact during the trial until one year after cessation of trial medication. Results: The clinical status was confirmed in 1819/1824 (99.7%) participants who were alive at the end of the trial, and in 100% of those participants still taking trial medication at the end of the trial. During post-trial follow up, 515 patients (28.2%) were taking non-study colchicine, including 278 (30.5%) originally randomized to colchicine and 237 (25.9%) randomized to placebo. Over the entire follow-up period that included the 12-month period after the trial medication was ceased, the effect of prior exposure to colchicine on the primary CV outcome was still evident (2.2 vs 3.8 events per 100 person years, HR 0.58; 95% CI 0.45–0.74), however no post-trial CV benefit were apparent in the landmark analysis (3.3 vs 3.4 events per 100 person years, HR 0.97; 95% CI 0.56–0.1.69). Over the entire course of follow-up the incidence of new cancer (7.9% vs 7.2% RR 0.91; 95% CI 0.66–1.25) and non-CV death (0.9 vs 0.6 events per 100 person years, HR 1.44; 95% CI 0.92–2.27) was no different in the treatment groups. Conclusion: Although the CV benefits of colchicine treatment that emerged during the trial were still evident in the year after stopping study treatment, no additional CV benefit accrued after it was ceased. These data suggest that colchicine should be continued long-term to maximize its CV benefits. FUNDunding Acknowledgement: Type of funding sources: None.